2014
DOI: 10.1017/s1368980014002043
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake and nutritional risk in Mediterranean adolescents in relation to the severity of the eating disorder

Abstract: Objective: To assess the relationship between the degree of severity of eating disorders (ED) and energy and nutrient intakes and nutritional risk in a mixed-sex adolescent population without clinical symptoms. Design: Cross-sectional study. Setting: Data were collected in schools. Subjects: Adolescents (n 495) aged 14·2 (SD 1·0) years. The Eating Attitudes Test was used to detect adolescents at risk of ED (rED) and a structured interview based on the criteria of the Diagnostic and Statistical Manual of Mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…These questionnaires gave us information about servings per week and per month. The grams per day of each item were calculated in relation to the age of the participants and the size of the recommended ration as stipulated by the regional health authority [ 51 ] and in agreement with the experts in this field in our research group [ 52 , 53 , 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…These questionnaires gave us information about servings per week and per month. The grams per day of each item were calculated in relation to the age of the participants and the size of the recommended ration as stipulated by the regional health authority [ 51 ] and in agreement with the experts in this field in our research group [ 52 , 53 , 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…The selected studies were published from 1991 to 2020 and conducted in the USA (n 8) (24,25,28,29,39,42,44,45,48) , Brazil (n 3) (31,34,35,37) , Spain (n 3) (25)(26)(27) , Canada (n 2) (28,29) , Taiwan (n 2) (30,31) , Australia (n 1) (32) , Ireland (n 1) (33) , Sweden (n 1) (34) , Japan (n 1) (35) , Germany (n 1) (36) and England (n 1) (37) (Fig. 2).…”
Section: Characteristics Of the Evidence Sourcesmentioning
confidence: 99%
“…Although the inclusion criterion had a maximum age of 19 years, we admitted three studies that had an age group between 12 and 20 years (24,25,44,45) . Thirteen studies involved female subjects (24)(25)(26)28,32,34,35,37,39,40,(42)(43)(44)46,48) and eleven recruited participants of both sexes (24)(25)(26)(27)(28)(29)33,34,36,38,39) . Few studies (n 4) reported the race/ethnicity of the participants (24,25,27,43,45) .…”
Section: Characteristics Of the Evidence Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…In eating disorders, dietary restriction typically presents alongside rigidity in eating patterns, food rules and categorisation of foods as 'good' or 'bad'. Dietary restriction may lead to restriction of specific foods or food groups, such as meats, grain-based foods or dairy products, resulting in poor dietary variety and inadequate intake of a range of macronutrients and micronutrients (Aparicio et al, 2015;Aparicio-Llopis et al, 2014).…”
Section: What Role Does Dietary Restriction Play In the Development Of Eating Disorders?mentioning
confidence: 99%